Tingkat Kemampuan Hubungan Sosial di Tinjau dari Jenis Kelamin, Latar Belakang Budaya dan Implikasi dalam Bimbingan dan Konseling - Hardianti, Susi; Kiram, Yanuar; Syahniar, Syahniar (Konselor, 2014)
the social relationship ability can be defined as a person capability to speak (communication ability), to express his or her feeling or problems faced and to figure out the solution adaptively. This research was designed for describing the students’ ability to build social relationship viewed from sex and cultural background. This was a descriptive comparative research which applied quantitative approach. This research was conducted to the students at SMAN 01, SMAN 05, and SMAN 07 Kab. Mukomuko. The number of the population was 442 student. By using purposive sampling technique, 210 of them were taken as the sample. The instrument of the research was a questionnaire of Likert scale whose reliability was 0,958. The result of the research indicated that: 1) the ability of both male and female students in building social relationship was high, 2) the ability of the students having both majority and minority cultural background in building social relationship was high, 3) there was a significant difference between the in building social relationship of the male and the female students, 4) there was a significant difference between the in building social relationship of the students having majority and minority cultural background.